Cytologic diagnosis of gastric submucosal lesions by endoscopic ultrasound-guided fine-needle aspiration: A single center experience in Saudi Arabia - Emad Raddaoui; Majid A Almadi; Abdulrahman M Aljebreen; Faisal Alsaif (Wolters Kluwer Medknow Publications, 2015)
Background and Aims: Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) sampling has become standard practice for the diagnosis of submucosal gastrointestinal (GI) lesions. The aim of this study was to determine the utility of EUS-guided FNA cytology in the diagnosis of deeply seated gastric mass lesions. Materials and Methods: Thirteen patients with deeply seated gastric mass lesions were diagnosed by EUS-FNA. Adequate cytology material was present in all cases. Cell blocks were available in 10 cases. Surgical resections were performed in 8 cases. Immunohistochemical (IHC) studies were done on cell blocks in 9 cases and on 6 resected specimens. Seven cases has proved to be GI stromal tumors (GIST), in four of them, cell blocks were available, and resection for GIST was performed in 5 cases. IHC stains that were performed in cytology, as well as resection specimens, revealed similar results in each patient. Conclusion: EUS-FNA cytology, when combined with a histologic assessment of cell blocks provides accurate and efficient tissue diagnosis of a wide variety of deeply seated gastric mass lesions.